2019
DOI: 10.2147/idr.s208757
|View full text |Cite
|
Sign up to set email alerts
|

<p>Indole-core-based novel antibacterial agent targeting FtsZ</p>

Abstract: Background The prevalence of drug-resistant bacterial infections urges the development of new antibacterial agents that possess a mechanism of action different from traditional antibiotics. FtsZ has been recognized as a key functional protein in bacterial cell division and it is currently believed to be a potential target for the development of novel antibacterial agents. Purpose The primary aim of the study is to screen out an inhibitor targeting at FtsZ and followed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…In both infection models, the treatment with various indoline-2-one derivates was associated with an increased host cell survival. As previously described we could not detect any growth-inhibitory effect of indoline-2-ones on Pa or S T. [ 32 ]. However, indole and indoline derivates such as 7-fluoroindole are known to inhibit a series of virulence factors of Pa such as quorum sensing, swarming and synthesis of pyocyanin, pyochelin and pyoverdine [ 29 ].…”
Section: Discussionsupporting
confidence: 47%
“…In both infection models, the treatment with various indoline-2-one derivates was associated with an increased host cell survival. As previously described we could not detect any growth-inhibitory effect of indoline-2-ones on Pa or S T. [ 32 ]. However, indole and indoline derivates such as 7-fluoroindole are known to inhibit a series of virulence factors of Pa such as quorum sensing, swarming and synthesis of pyocyanin, pyochelin and pyoverdine [ 29 ].…”
Section: Discussionsupporting
confidence: 47%
“…The efficacies of indole derivatives such as 2, 5, 6-and 2, 5, 7-trisubstituted benzimidazoles in M. tuberculosis, S. aureus, and B. subtilis are reflected by their abilities to target a key functional protein in bacterial cell division like FtsZ. In the same study, it was hypothesized that these derivatives bound in the interdomain cleft of FtsZ, interrupted GTPase activity, stimulated FtsZ polymerization, and ultimately inhibiting bacterial cell division [55]. Since 5-iodoindole decreased cell size of E. coli strains and C. albicans (Figure 8) and was found to rapidly kill A. baumannii (Figure 4), other microbes (Figure 7), three nematode species [24][25][26][27], and an insect [25], but not plants or vertebrates [25,26], it would appear that 5-iodoindole is selectively transported through the membranes of bacteria, fungi, and nematodes and then specifically targets DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid 93 (MIC: 2.0–4.0 μg/ml) possessed an excellent activity against both drug‐sensitive ( B. subtilis , S. aureus , S. epidermidis , and E. faecalis ) and drug‐resistant (four MRSA, ampicillin‐resistant S. aureus , VRE, and vancomycin‐resistant E. faecium ) strains, and the activity was far superior to that of berberine (MIC: ≥96 μg/ml). [ 194 ] The mechanistic study revealed that hybrid 93 was able to disrupt FtsZ polymerization and inhibit GTPase activity and cell division, so this hybrid could act as a lead compound for the discovery of novel antibacterial agents targeting FtsZ to fight against multidrug‐resistant bacteria.…”
Section: Miscellaneous Indole/isatin Hybridsmentioning
confidence: 99%